Respon Bawang Merah Varietas Bima Terhadap Aplikasi Mikoriza dan Pupuk Organik Cair Limbah Rumah Tangga: Respon Bawang Merah Varietas Bima Terhadap Aplikasi Mikoriza dan Pupuk Organik Cair Limbah Rumah Tangga - Daryanti; Soelistijono, R.; Mardhika Sari, Siti; Soemarah Kurnia Dewi, Tyas; Restu Putra Abadi, Pramudika (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2025)
Shallots are a horticultural commodity whose demand is always increasing. Organic cultivation by utilizing household waste as organic fertilizer and mycorrhizae is one way to increase the production of Bima variety shallots. The study was conducted from February to May 2025 in Koripan Village, Matesih District, Karanganyar Regency. This study aimed to determine the effect of mycorrhizae and liquid organic fertilizer (POC) from household waste on the growth and yield of Bima variety shallots. The study was conducted using a Completely Randomized Block Design (RAKL) using two factors, namely the mycorrhizae dose (0, 5, and 10 grams) and the POC watering interval (0, 3, 6, and 9 days). The results showed that the administration of 10 grams of mycorrhizae gave the best results in terms of bulb weight (32.75 grams), number of bulbs (7.20), and consumption bulb weight (31.12 grams). Meanwhile, the three-day POC watering interval (P2) resulted in the highest tuber weight (36.83 grams), tuber number (8.00 grams), and tuber consumption weight (35.44 grams) of all treatments. The combination of mycorrhizal treatment and POC watering interval significantly increased plant productivity in an organic and environmentally friendly manner.